A low-carbon high-temperature resistant flame retardant material and preparation method thereof
By using composite shielding agents with layered structure and component doping characteristics in low-carbon high-temperature flame retardant materials, the problem of water branches forming and growth in high-temperature and high-humidity environment of coal mines is solved, and the durability of the cable is significantly improved. and adaptability.
Patent Information
- Application Number
- CN202411457382.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-18
AI Technical Summary
Existing low-carbon high-temperature flame retardant materials are prone to problems of water branches in high-temperature and high-humidity environments of coal mines, resulting in reduced cable transmission capacity and shortened service life.
Use low-carbon high-temperature flame retardant materials composed of low-density polyethylene, flame retardant, talc powder, composite shielding agent, etc., and use the preparation steps of composite shielding agent, including the modification liquid treatment of montmorillonite, polymerization reaction and nanometers. Barium titanate doping, a composite shielding agent with layered structure and component doping characteristics was prepared. The composite shielding agent plays a role in suppressing the directional movement of water molecules and the formation of water branches under the action of high electric fields in the cable insulation layer.
It significantly enhances the resistance of the cable insulation layer to invade water branches, extends the service life of the cable, and shows strong adaptability in high temperature and high humidity environments of coal mines.
Smart Images

Figure FT_1 
Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of flame retardant materials, and more specifically, to a low-carbon, high-temperature resistant flame retardant material and a preparation method thereof. Background Art
[0002] Low-carbon high-temperature flame-retardant material is a material that has both high-temperature resistance and good flame-retardant properties, and is also low-carbon and environmentally friendly. It is widely used in aerospace, energy, automobile, electronics and other fields, and its application in the cable field is also relatively mature.
[0003] The cable is mainly composed of three parts: cable body, insulation layer and sheath layer. The cable body is mainly a copper core, which plays the role of transmitting current; the insulation layer and sheath layer are made of polyethylene, rubber and other raw materials, with pigments and other additives added, and are prepared through a mixed cross-linking process or a vulcanization process, which plays the role of protecting the internal cable body and isolating the conductor from the outside world. Low-carbon high-temperature resistant flame-retardant materials are mainly used in the insulation layer and sheath layer. Among them, the cable sheath layer and insulation layer made of cross-linked polyethylene as raw material are more commonly used in AC cables.
[0004] Due to the physical and chemical properties of cross-linked polyethylene, such as heat resistance, low power loss during transmission, high hardness, and chemical corrosion resistance, its application in AC cables is relatively mature. However, this type of material also has limitations in application scenarios, especially in the humid and high-temperature environment of coal mines. In the high temperature and humidity of coal mines, due to the high moisture content in the environment and the high field strength inside the AC cable, it is easy for water dendrites to form inside the insulation layer of the AC cable made of cross-linked polyethylene. The generation and growth of water dendrites will cause a decrease in the transmission capacity of the cable, lead to cable aging, and reduce the operating life of the cable.
[0005] The formation of water dendrites in cables is mainly caused by the high electric field in the cable and the water molecules in the environment. When transmitting alternating current, there is a high field strength inside the cable. This high field strength easily induces polar water molecules in the air to invade the cable, causing damage to the cable core. Therefore, it is usually necessary to coat the cable core with an insulating layer and a sheath layer. On the one hand, this can weaken the field strength of the outer layer of the cable, and at the same time, it can protect the cable and prevent the invasion of external moisture. However, once the cable cracks due to external stress or its own aging, water molecules will invade the cable along the cable defects and migrate to the inner layer of the cable under the action of high field strength. The water molecules are arranged in a direction and continue to grow in the cable insulation layer, finally causing the insulation breakdown of the cable, resulting in a decrease in the transmission capacity of the cable. Therefore, inhibiting the growth of water dendrites in the insulation layer is crucial for the long-term use of the cable.
[0006] A Chinese patent application document with application publication number CN104347174A discloses a waterproof cable. This solution improves the waterproof effect, reduces the ease with which water enters the cable insulation layer, and inhibits the formation of water dendrites by adding a plastic-coated aluminum alloy waterproof layer between the cable insulation layer and the sheath layer.
[0007] Although the above application documents have made useful attempts to inhibit water from invading the cable insulation layer, the preparation method according to this scheme requires an additional extrusion process to be added to the cable, which increases the cost and cycle of industrial production. Therefore, the problem of finding a low-cost method to weaken the formation and growth of water dendrites still exists. Summary of the invention
[0008] In order to further reduce the generation and growth of water dendrites in the cable insulation layer, the present application provides a low-carbon, high-temperature resistant, flame-retardant material and a preparation method thereof.
[0009] In the first aspect, the present application provides a low-carbon high-temperature resistant flame-retardant material, which is made of the following raw materials in parts by weight: 75-80 parts of low-density polyethylene, 10-25 parts of flame retardant, 10-15 parts of talc, 5-10 parts of composite shielding agent, 2-5 parts of cross-linking agent, 3-5 parts of plasticizer, 1-2 parts of antioxidant, and 0.5-1 parts of stabilizer;
[0010] The preparation steps of the composite shielding agent are as follows:
[0011] (1) mixing water, ethanol, dodecyltrimethylammonium bromide, dodecylmethylammonium chloride, and dimethyl sulfoxide to obtain a modified liquid, using the modified liquid to swell the montmorillonite, then separating the solid from the liquid, washing and drying the solid, and obtaining an organic modified montmorillonite;
[0012] (2) mixing organic modified montmorillonite, dispersant, dodecyl sulfonic acid, dodecylbenzene sulfonic acid, aniline monomer and acetone, adjusting the pH, adding ammonium persulfate, performing polymerization reaction, then performing solid-liquid separation, washing the solid part, and drying to obtain a polyaniline-montmorillonite composite;
[0013] (3) The polyaniline-montmorillonite composite, nano-barium titanate, dispersant and water are uniformly mixed, stirred, centrifuged, the solid part is filtered out, and dried to obtain a composite shielding agent.
[0014] By adopting the above technical scheme, the prepared low-carbon high-temperature flame-retardant material has a good effect of inhibiting water dendrites, wherein the composite shielding agent used is a layered material with components intermixed with each other, which can play a role in inhibiting the high electric field in the cable. Within the field strength range of the AC cable, the composite structure of polyaniline-montmorillonite can convert the energy of the alternating electric field into molecular internal energy through thermoelectric conversion, and the converted internal energy finally escapes into the surrounding environment in the form of Joule heat. The nano-barium titanate in the composite shielding agent is a temperature-sensitive dielectric material, and the Joule heat generated by the polyaniline-montmorillonite composite in the alternating electric field is absorbed by the nano-barium titanate, and the dielectric constant of the nano-barium titanate increases. This temperature-sensitive dielectric effect acts on the composite shielding agent uniformly distributed in the entire cable insulation layer, driving the overall dielectric constant of the cable insulation layer material to increase. The increase in the dielectric constant of the insulation layer propagation medium will cause the field strength in the cable insulation layer to decrease, and the speed of the directional migration of polar water molecules affected by the high field strength in the cable will also slow down, and finally achieve the effect of inhibiting the growth of water dendrites.
[0015] Preferably, in step (1), the mass volume ratio of water, ethanol, dodecyltrimethylammonium bromide, dodecylmethylammonium chloride and dimethyl sulfoxide is (135-150) mL: (25-30) mL: (2-2.5) g: (3-4) g: (8-10) mL.
[0016] By adopting the above technical solution and using the modified liquid prepared with the above components and proportions of raw materials to treat montmorillonite, the montmorillonite can be swollen and the interlayer distance of the montmorillonite can be effectively increased, which is convenient for the subsequent in-situ polymerization operation of aniline monomer.
[0017] Preferably, in step (1), the temperature of the swelling treatment is set to 40-60°C.
[0018] By adopting the above technical solution, the swelling effect of montmorillonite is affected by temperature. When the temperature is lower than 40°C, the thermodynamic motive force of the intercalant entering the montmorillonite interlayer is small, resulting in a low degree of swelling of the montmorillonite. Through experiments combined with the results of aniline polymerization in subsequent steps, the swelling effect of montmorillonite is best when the swelling treatment temperature is in the temperature range of 40-60°C.
[0019] Preferably, in step (2), the mass volume ratio of ammonium persulfate, dodecyl sulfonic acid, dodecylbenzene sulfonic acid and aniline monomer is (24-26) g: (8-12) g: (4-5) g: (11-12.5) mL.
[0020] By adopting the above technical solution, the interlayer spacing of the organically modified montmorillonite is enlarged, and the aniline monomer can enter the interlayer of the montmorillonite and carry out in-situ polymerization under the action of the initiator ammonium persulfate, and a composite material is obtained after the reaction is completed. Under the above ratio of initiator ammonium persulfate, emulsifier dodecyl sulfonic acid and dodecylbenzene sulfonic acid, and aniline monomer, the in-situ polymerization effect of aniline on the organically modified montmorillonite is the best.
[0021] Preferably, in the step (2), the polymerization reaction time is set to 8-10 hours.
[0022] By adopting the above technical solution, when the aniline polymerization reaction time is 8-10 hours, the polymerization is relatively complete.
[0023] Preferably, in step (3), the average particle size of nano-barium titanate is 150-200 nm.
[0024] By adopting the above technical solution, nano-scale barium titanate has a large heat absorption area, making the utilization of its dielectric temperature sensitivity the highest. When the average particle size of nano-barium titanate is in the range of 150-200nm, nano-barium titanate can be more evenly doped between the polyaniline-montmorillonite composite, which not only inhibits the agglomeration of the polyaniline-montmorillonite composite, but also enables the composite shielding agent to exhibit better sliding characteristics, so that the composite shielding agent can be more evenly dispersed in the cable insulation layer and show good use effect.
[0025] Preferably, in the step (3), the mass ratio of nano-barium titanate to the polyaniline-montmorillonite composite is (3-4):(1-1.5).
[0026] By adopting the above technical scheme, the interaction between the dielectric property of nano-barium titanate and the thermoelectric property of polyaniline-montmorillonite composite can reach a certain degree of balance. When the mass fraction of nano-barium titanate in the composite insert layer agent is too large as the dielectric component in the composite shielding agent, the thermoelectric conversion of the polyaniline-montmorillonite composite will be inhibited, the Joule heat generated by the thermoelectric conversion will be reduced, and the heat absorbed by nano-barium titanate will also be reduced, so that the dielectric temperature-sensitive effect of nano-barium titanate cannot be well exerted. Through experiments, when the mass ratio of nano-barium titanate to polyaniline-montmorillonite composite is (3-4): (1-1.5), the synergistic effect of the two has the best effect on the cable electric field shielding.
[0027] Preferably, in step (3), the centrifugal speed is 5000-7000 rpm and lasts for 30-45 min.
[0028] By adopting the above technical solution, the centrifugal state of the nano-barium titanate and polyaniline-montmorillonite composite is optimal.
[0029] In a second aspect, the present application provides a method for preparing a low-carbon, high-temperature resistant, flame-retardant material, the steps of which are as follows:
[0030] (S01) mixing: low-density polyethylene, plasticizer, talcum powder, and flame retardant are added to an internal mixer and mixed to obtain a rubber compound;
[0031] (S02) Cross-linking molding: The antioxidant, cross-linking agent, composite shielding agent, stabilizer and rubber compound are mixed, the temperature is increased for cross-linking, and the rubber compound is repeatedly returned to the rubber compound for cooling to obtain a low-carbon, high-temperature resistant and flame-retardant material.
[0032] In summary, this application has the following beneficial effects:
[0033] 1. The present application prepares a composite shielding agent having both thermoelectric and dielectric effects. The composite shielding agent is applied to the insulation layer of an AC cable to significantly enhance the material's ability to resist water tree intrusion.
[0034] 2. Nano barium titanate and polyaniline-montmorillonite composite can play a combined effect in the composite shielding agent prepared in the present application. On the one hand, the polyaniline formed after the polymerization of aniline is a material that is sensitive to electric field changes. By the intercalation combination of aniline and montmorillonite, when the AC cable is running and produces an alternating electric field, the polyaniline is inductively induced by the alternating electric field, and the p electron conjugation and the resonance between the montmorillonite layers convert the energy of the cable alternating electric field into the energy of molecular vibration, producing Joule heat. On the other hand, the AC cable field strength is related to the dielectric constant of the propagation medium, and decreases along with the rising of the dielectric constant of the propagation medium. The Joule heat produced by the polyaniline-montmorillonite composite in the present application can promote the temperature rise of the temperature-sensitive dielectric material nano barium titanate, and the rising of temperature causes the increase of the dielectric constant of nano barium titanate again. This temperature-sensitive dielectric effect acts on the composite shielding agent evenly distributed throughout the cable insulation layer, driving the overall dielectric constant of the cable insulation layer material to increase, and ultimately significantly reducing the cable field strength in the insulation layer, thereby achieving the effect of inhibiting the directional movement of water molecules in the insulation layer and the formation of water dendrites.
[0035] 3. The cable insulation layer prepared by using the composite shielding agent of the present application has excellent performance in resisting the growth of water trees, and the AC cable prepared by using the composite shielding agent has strong adaptability to the high temperature and high humidity environment of coal mines. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a line graph of the water tree growth lengths of the low-carbon, high-temperature resistant flame retardant materials prepared in Example 1-3 and Comparative Example 1-2 at 3d, 9d, 15d, and 21d in the water needle electrode method accelerated water tree aging test. DETAILED DESCRIPTION
[0037] Example 1
[0038] In this embodiment, the low-carbon high-temperature resistant flame retardant material is made of the following raw materials by weight: 750g of low-density polyethylene, 250g of aluminum hydroxide high white powder, 100g of talcum powder, 50g of composite shielding agent, 5g of epoxy fatty acid butyl ester, 30g of stearic acid, 20g of diisopropyl peroxide, 5g of antioxidant 300, 5g of antioxidant 1010, 5g of 4-n-propyl benzoic acid, and 5g of diallyl phthalate;
[0039] The preparation steps of the composite shielding agent of this embodiment are as follows:
[0040] (1) 18 g of sodium montmorillonite, 135 mL of deionized water, 25 mL of anhydrous ethanol, 2 g of dodecyltrimethylammonium bromide, 3 g of decylmethylammonium chloride, and 8 mL of dimethyl sulfoxide were placed in a 500 mL three-necked flask, the temperature was controlled at 55 ° C, the magnetic stirring speed was 150 rpm, and the treatment was performed for 8 h. Then, the solid-liquid separation was performed, and the precipitate was washed twice with anhydrous ethanol and dried in a vacuum oven at 45 ° C for 2 h to obtain an organic modified montmorillonite.
[0041] (2) Take a 500 mL three-necked flask, mix the organic modified montmorillonite in step (1), 0.02 g of dispersant sodium tripolyphosphate, 8 g of dodecyl sulfonic acid, 4 g of dodecylbenzene sulfonic acid and 12 mL of aniline monomer, then add 200 mL of acetone to the system, control the stirring speed to 50 rpm, stir for 20 min, adjust the pH of the system to 5, then add 24 g of ammonium persulfate to the system to dissolve, control the system temperature to 22° C., react for 8 h, filter and collect the precipitate, repeatedly rinse the precipitate with anhydrous ethanol twice to remove excess aniline monomer, and obtain a polyaniline-montmorillonite composite.
[0042] (3) Take a 250mL three-necked flask, mix 10g of the polyaniline-montmorillonite composite prepared in step (2), 30g of nano barium titanate (150nm), 0.05g of dispersant sodium tripolyphosphate, and 150mL of deionized water, control the magnetic stirring speed to 350rpm, and continue for 25min, then transfer the mixed solution to a low-speed centrifuge, control the centrifugal speed to 5000rpm, and continue for 30min to remove the deionized water on the surface of the precipitated product, then place the centrifugal product in a Buchner funnel padded with a filter membrane, slowly add 30mL of anhydrous ethanol along the wall of the funnel, connect a vacuum filtration device, set the vacuum degree to 0.001Mpa, filter for 10min, repeat the filtration twice, and stop filtration when the anhydrous ethanol in the distillation flask is basically drained, let it stand for 2h, evaporate the remaining anhydrous ethanol, and obtain a composite shielding agent after drying.
[0043] The preparation steps of the low-carbon high-temperature resistant flame retardant material of this embodiment are as follows:
[0044] (S01) Mixing: accurately weigh low-density polyethylene, diallyl phthalate, stearate, talcum powder, and aluminum hydroxide high-white micropowder, put them into an internal mixer, mix them at a temperature of 130° C. for 15 minutes, and obtain a mixed rubber;
[0045] (S02) Cross-linking molding: Antioxidant 300, antioxidant 1010, diisopropylbenzene peroxide, composite shielding agent, epoxy fatty acid butyl ester and 4-n-propyl benzoic acid are accurately weighed and put into an internal mixer, and mixed evenly with the rubber compound prepared in (S01). The temperature of the reaction system is controlled at 170°C, and the reaction is carried out for 30 minutes. Then, the debonding is started at 105°C. After debonding, the debonding is returned to the mixer for 3 times to make the components evenly mixed. Then, the mixture is allowed to stand and cool for 2 hours to obtain a low-carbon, high-temperature resistant and flame-retardant material.
[0046] Among them, low-density polyethylene (model: 1850A) was provided by Guangdong Zhonghai Nanlian Energy Co., Ltd. Sodium montmorillonite (model: PGW, interlayer spacing 1.2-1.4nm, specific surface area 735m 2 / g) provided by NANOCOR. Nano-barium titanate (purity 99%, density 6.08g / m 2 ) was provided by Yumu (Ningbo) New Materials Co., Ltd. The filter membrane (filter diameter: 50nm) was provided by Shanghai Ruiying International Trade Co., Ltd. Aluminum hydroxide high white powder (model: JWN-AOH-WF5, Al(OH)3 content ≥99.8%) was provided by Ningbo Jiweinano New Materials Technology Co., Ltd.
[0047] Example 2
[0048] The low-carbon high-temperature resistant flame-retardant material in this embodiment is made of the following raw materials by weight: 800 g of low-density polyethylene, 250 g of aluminum hydroxide, 100 g of talcum powder, 70 g of composite shielding agent, 50 g of epoxy fatty acid butyl ester, 40 g of stearic acid, 20 g of dicumyl peroxide, 5 g of antioxidant 300, 5 g of antioxidant 1010, 5 g of 4-n-propyl benzoic acid, and 5 g of diallyl phthalate;
[0049] The preparation steps of the composite shielding agent of this embodiment are as follows:
[0050] (1) 18 g of sodium montmorillonite, 135 mL of deionized water, 25 mL of anhydrous ethanol, 2 g of dodecyltrimethylammonium bromide, 3 g of decylmethylammonium chloride, and 8 mL of dimethyl sulfoxide were placed in a 500 mL three-necked flask, the temperature was controlled at 58 ° C, the magnetic stirring speed was 150 rpm, and the treatment was performed for 8 h. Then, the solid-liquid separation was performed, and the precipitate was washed twice with anhydrous ethanol and dried in a vacuum oven at 45 ° C for 2 h to obtain an organic modified montmorillonite.
[0051] (2) Take a 500 mL three-necked flask, mix the organic modified montmorillonite in step (1), 0.02 g of dispersant sodium tripolyphosphate, 10 g of dodecyl sulfonic acid, 4 g of dodecylbenzene sulfonic acid and 12 mL of aniline monomer, then add 200 mL of acetone to the system, control the stirring speed to 50 rpm, stir for 20 min, adjust the pH of the system to 5, then add 25 g of ammonium persulfate to the system to dissolve, control the system temperature to 22° C., react for 9 h, filter and collect the precipitate, repeatedly rinse the precipitate with anhydrous ethanol twice to remove excess aniline monomer, and obtain a polyaniline-montmorillonite composite.
[0052] (3) Take a 250mL three-necked flask, mix 15g of the polyaniline-montmorillonite composite prepared in step (2), 45g of nano barium titanate (150nm), 0.05g of dispersant sodium tripolyphosphate, and 150mL of deionized water, control the magnetic stirring speed to 350rpm, and continue for 25min, then transfer the mixed solution to a low-speed centrifuge, control the centrifugal speed to 6000rpm, and continue for 35min to remove the deionized water on the surface of the precipitated product, then place the centrifugal product in a Buchner funnel padded with a filter membrane, slowly add 30mL of anhydrous ethanol along the wall of the funnel, connect a vacuum filtration device, set the vacuum degree to 0.001Mpa, filter for 10min, repeat the filtration twice, and stop filtration when the anhydrous ethanol in the distillation flask is basically drained, let it stand for 2h, evaporate the remaining anhydrous ethanol, and obtain a composite shielding agent after drying.
[0053] The preparation steps of the low-carbon high-temperature resistant flame retardant material of this embodiment are as follows:
[0054] (S01) Mixing: accurately weigh low-density polyethylene, diallyl phthalate, stearate, talcum powder, and aluminum hydroxide high-white micropowder, put them into an internal mixer, mix them at a temperature of 130° C. for 15 minutes, and obtain a mixed rubber;
[0055] (S02) Cross-linking molding: Antioxidant 300, antioxidant 1010, diisopropylbenzene peroxide, composite shielding agent, epoxy fatty acid butyl ester and 4-n-propyl benzoic acid are accurately weighed and put into an internal mixer, and mixed evenly with the rubber compound prepared in (S01). The temperature of the reaction system is controlled at 170°C, and the reaction is carried out for 30 minutes. Then, the debonding is started at 105°C. After debonding, the debonding is returned to the mixer for 3 times to make the components evenly mixed. Then, the mixture is allowed to stand and cool for 2 hours to obtain a low-carbon, high-temperature resistant and flame-retardant material.
[0056] Among them, low-density polyethylene (model: 1850A) was provided by Guangdong Zhonghai Nanlian Energy Co., Ltd. Sodium montmorillonite (model: PGW, interlayer spacing 1.2-1.4nm, specific surface area 735m 2 / g) provided by NANOCOR. Nano-barium titanate (purity 99%, density 6.08g / m 2) was provided by Yumu (Ningbo) New Materials Co., Ltd. The filter membrane (filter diameter: 50nm) was provided by Shanghai Ruiying International Trade Co., Ltd. Aluminum hydroxide high white powder (model: JWN-AOH-WF5, Al(OH)3 content ≥99.8%) was provided by Ningbo Jiweinano New Materials Technology Co., Ltd.
[0057] Example 3
[0058] The low-carbon high-temperature resistant flame-retardant material in this embodiment is made of the following raw materials by weight: 780 g of low-density polyethylene, 200 g of aluminum hydroxide, 100 g of talcum powder, 100 g of composite shielding agent, 50 g of epoxy fatty acid butyl ester, 30 g of stearic acid, 30 g of dicumyl peroxide, 5 g of antioxidant 300, 5 g of antioxidant 1010, 5 g of 4-n-propyl benzoic acid, and 5 g of diallyl phthalate;
[0059] The preparation steps of the composite shielding agent of this embodiment are as follows:
[0060] (1) 18 g of sodium montmorillonite and 135 mL of deionized water, 25 mL of anhydrous ethanol, 2 g of dodecyltrimethylammonium bromide, 3 g of decylmethylammonium chloride, and 8 mL of dimethyl sulfoxide were placed in a 500 mL three-necked flask, the temperature was controlled at 58 ° C, the magnetic stirring speed was 150 rpm, and the treatment was performed for 8 h. Then, the solid-liquid separation was performed, and the precipitate was washed twice with anhydrous ethanol and dried in a vacuum oven at 45 ° C for 2 h to obtain organic modified montmorillonite.
[0061] (2) Take a 500 mL three-necked flask, mix the organic modified montmorillonite in step (1), 0.02 g of dispersant sodium tripolyphosphate, 10 g of dodecyl sulfonic acid, 4 g of dodecylbenzene sulfonic acid and 12 mL of aniline monomer, then add 200 mL of acetone to the system, control the stirring speed to 50 rpm, stir for 20 min, adjust the pH of the system to 5, then add 25 g of ammonium persulfate to the system to dissolve, control the system temperature to 22° C., react for 9 h, filter and collect the precipitate, repeatedly rinse the precipitate with anhydrous ethanol twice to remove excess aniline monomer, and obtain a polyaniline-montmorillonite composite.
[0062] (3) Take a 250mL three-necked flask, mix 15g of the polyaniline-montmorillonite composite prepared in step (2), 45g of nano barium titanate (200nm), 0.05g of dispersant sodium tripolyphosphate, and 150mL of deionized water, control the magnetic stirring speed to 350rpm, and continue for 25min, then transfer the mixed solution to a low-speed centrifuge, control the centrifugal speed to 6000rpm, and continue for 35min to remove the deionized water on the surface of the precipitated product, then place the centrifugal product in a Buchner funnel padded with a filter membrane, slowly add 30mL of anhydrous ethanol along the wall of the funnel, connect a vacuum filtration device, set the vacuum degree to 0.001Mpa, filter for 10min, repeat the filtration 3 times, and stop filtration when the anhydrous ethanol in the distillation flask is basically drained, let it stand for 2h, evaporate the remaining anhydrous ethanol, and obtain a composite shielding agent after drying.
[0063] The preparation steps of the low-carbon high-temperature resistant flame retardant material of this embodiment are as follows:
[0064] (S01) Mixing: accurately weigh low-density polyethylene, diallyl phthalate, stearate, talcum powder, and aluminum hydroxide high-white micropowder, put them into an internal mixer, mix them at a temperature of 130° C. for 15 minutes, and obtain a mixed rubber;
[0065] (S02) Cross-linking molding: Antioxidant 300, antioxidant 1010, diisopropylbenzene peroxide, composite shielding agent, epoxy fatty acid butyl ester and 4-n-propyl benzoic acid are accurately weighed and put into an internal mixer, and mixed evenly with the rubber compound prepared in (S01). The temperature of the reaction system is controlled at 170°C, and the reaction is carried out for 30 minutes. Then, the debonding is started at 105°C. After debonding, the debonding is returned to the mixer for 3 times to make the components evenly mixed. Then, the mixture is allowed to stand and cool for 2 hours to obtain a low-carbon, high-temperature resistant and flame-retardant material.
[0066] Among them, low-density polyethylene (model: 1850A) was provided by Guangdong Zhonghai Nanlian Energy Co., Ltd. Sodium montmorillonite (model: PGW, interlayer spacing 1.2-1.4nm, specific surface area 735m 2 / g) provided by NANOCOR. Nano-barium titanate (purity 99%, density 6.08g / m 2 ) was provided by Yumu (Ningbo) New Materials Co., Ltd. The filter membrane (filter diameter: 50nm) was provided by Shanghai Ruiying International Trade Co., Ltd. Aluminum hydroxide high white powder (model: JWN-AOH-WF5, Al(OH)3 content ≥99.8%) was provided by Ningbo Jiweinano New Materials Technology Co., Ltd.
[0067] Comparative Example 1
[0068] The difference between this comparative example and Example 1 is that an equal amount of montmorillonite is used to replace the composite shielding agent, and the rest is the same as Example 1.
[0069] Comparative Example 2
[0070] The difference between this comparative example and Example 1 is that the nano-barium titanate in the composite shielding agent is replaced by an equal amount of nano-titanium dioxide with the same particle size, and the rest is the same as Example 1.
[0071] Performance testing
[0072] Tensile strength test
[0073] Referring to the sample preparation method of GB / T9352 and the operating procedures of GB / T1040.2-2022, the prepared sample was placed in an insulating material tensile testing machine (model: WAW-20) for tensile testing, and the maximum initial stress during the stretching process was recorded. The test was repeated for 5 groups of data, and the average value of the maximum initial stress was taken as the final value.
[0074] Table 1
[0075]
[0076] Insulation resistance test
[0077] The rubber mixtures prepared in the embodiments of Examples 1-3 and Comparative Examples 1-2 are respectively put into the extruder, and the cable body is extruded after cross-linking. The extruder bevel head is adjusted to control the thickness of the extruded insulation layer to be 24 mm, and then the formed single-core cable is cooled at room temperature for 3-4 days to obtain a single-core cable without a sheath layer. The insulation resistance of the single-core cable without a sheath layer prepared in Examples 1-3 and Comparative Examples 1-2 is tested using an insulation resistance tester at a 5KV test voltage level, and then the cable is aged at 60°C for 10 days, and the insulation resistance of the aged cable is retested. Record the resistance absorption ratio at 15s and 60s after applying voltage under the two states, and test the insulation resistance value when stable under the two states.
[0078] Table 2
[0079]
[0080] Electric field strength test
[0081] The same insulation resistance test experiment operation is performed to obtain a single-core cable without a sheath layer. The cable is placed horizontally, and 500KV AC is applied to the cable through a high-voltage test transformer. The electric field strength tester (instrument model: LZT-1150) is placed close to the cable (the probe direction of the tester is perpendicular to the cable, and the vertical distance between the tester and the cable is kept at 5cm). The tester is set to low frequency gear, and after the voltage is turned on, wait for a moment, and after the reading is stable, record the reading on the digital display at this time. Then translate the tester to keep the cable distance the same as the first test distance, change the test position, test 3 groups of data, take the average value and record it, repeat the test 5 times, and take the maximum value of the 5 groups of average values as the final electric field strength Emax.
[0082] Table 3
[0083]
[0084] Water branch length test
[0085] The cup-shaped experimental device recommended by IEC / TS61956 standard was used to conduct accelerated water tree aging test on low-carbon high-temperature flame-retardant material samples by water needle electrode method. A sinusoidal AC voltage with a frequency of 400Hz and an effective value of 6KV was applied to the copper positive and negative electrodes of the cup-shaped experimental device to treat the pinhole defects of the low-carbon high-temperature flame-retardant material, and then placed at the bottom of the cup so that the pinhole defects were filled with solution to form a water needle electrode, which served as the starting point for the growth of water trees. The lower surface of the low-carbon high-temperature flame-retardant material sample was grounded through the lower copper electrode. The copper electrode was then placed in a sodium chloride solution with a mass concentration of 1.7 mol / L. The experiment was carried out at 20°C and the aging time was 21 days. The growth length of the water dendrites was tested on the 3rd, 9th, 15th and 21st days of aging. After the aging, a multi-function slicer (model: ABCH-QP150, slicing accuracy of ±5%) was used to cut slices with a thickness of approximately 500µm along the pinhole in a direction perpendicular to the surface of the low-carbon, high-temperature resistant flame retardant material sample, and the growth length of the water dendrites in the slices containing the pinholes was measured and recorded.
[0086] By analyzing Examples 1-3 and Comparative Examples 1-2 and combining them with Table 1-2, it can be seen that after adding the composite shielding agent, the tensile strength and aged insulation resistance of the cable insulation layer material are similar to those of the cable insulation layer material without adding the composite shielding agent. It can be concluded that the prepared cable insulation layer material meets the cable's requirements for the tensile strength and insulation performance of the insulation layer material.
[0087] By analyzing Examples 1-3 and Comparative Examples 1-2 and combining them with Table 3, it can be seen that after adding the composite shielding agent, the electric field strength of the cable in the insulating layer is significantly reduced compared to Comparative Examples 1-2, indicating that the composite shielding agent has a good shielding effect on the cable field strength, and the material prepared by the proportion and operation of Example 2 has the best effect on weakening the cable electric field.
[0088] Analyze Examples 1-3 and Comparative Examples 1-2 and combine Figure 1 It can be seen that only in the initial period of water tree aging, the cable insulation layer with the addition of the composite shielding agent can show a significant effect of slowing down the growth of water trees compared to comparative examples 1-2. After the aging is completed, embodiments 1-3 can still maintain a length of less than 200µm, and among the three embodiments, the material in embodiment 2 has the best effect in inhibiting the growth of water trees.
[0089] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A low-carbon, high-temperature resistant, flame-retardant material, characterized in that: The invention is made of the following raw materials in parts by weight: 75-80 parts of low-density polyethylene, 10-25 parts of flame retardant, 10-15 parts of talc, 5-10 parts of composite shielding agent, 2-5 parts of cross-linking agent, 3-5 parts of plasticizer, 1-2 parts of antioxidant and 0.5-1 parts of stabilizer; The preparation steps of the composite shielding agent are as follows: (1) mixing water, ethanol, dodecyltrimethylammonium bromide, dodecylmethylammonium chloride, and dimethyl sulfoxide to obtain a modified liquid, using the modified liquid to swell the montmorillonite, then separating the solid from the liquid, washing and drying the solid, and obtaining an organic modified montmorillonite; (2) mixing organic modified montmorillonite, dispersant, dodecyl sulfonic acid, dodecylbenzene sulfonic acid, aniline monomer and acetone, adjusting the pH, adding ammonium persulfate, performing polymerization reaction, then performing solid-liquid separation, washing the solid part, and drying to obtain a polyaniline-montmorillonite composite; (3) The polyaniline-montmorillonite composite, nano-barium titanate, dispersant and water are uniformly mixed, stirred, centrifuged, the solid part is filtered out, and dried to obtain a composite shielding agent.
2. A low-carbon, high-temperature resistant, flame-retardant material according to claim 1, characterized in that: In the step (1), the mass volume ratio of water, ethanol, dodecyltrimethylammonium bromide, dodecylmethylammonium chloride and dimethyl sulfoxide is (135-150) mL: (25-30) mL: (2-2.5) g: (3-4) g: (8-10) mL.
3. The low-carbon, high-temperature resistant, flame-retardant material according to claim 1, characterized in that: In the step (1), the temperature of the swelling treatment is set at 40-60°C.
4. The low-carbon high-temperature resistant flame retardant material according to claim 1, characterized in that: In the step (2), the mass volume ratio of ammonium persulfate, dodecyl sulfonic acid, dodecylbenzene sulfonic acid, and aniline monomer is (24-26) g: (8-12) g: (4-5) g: (11-12.5) mL.
5. The low-carbon high-temperature resistant flame retardant material according to claim 1, characterized in that: In the step (2), the polymerization reaction time is set to 8-10 hours.
6. The low-carbon high-temperature resistant flame retardant material according to claim 1, characterized in that: In the step (3), the average particle size of the nano-barium titanate is 150-200 nm.
7. The low-carbon, high-temperature resistant, flame-retardant material according to claim 1, characterized in that: In the step (3), the mass ratio of nano-barium titanate to the polyaniline-montmorillonite composite is (3-4):(1-1.5).
8. The low-carbon, high-temperature-resistant, flame-retardant material according to claim 1, characterized in that: In the step (3), the centrifugal speed is 5000-7000 rpm and lasts for 30-45 min.
9. A method for preparing a low-carbon, high-temperature resistant, flame-retardant material as claimed in any one of claims 1 to 8, characterized in that: The steps include: (S01) mixing: low-density polyethylene, plasticizer, talcum powder, and flame retardant are added to an internal mixer and mixed to obtain a rubber compound; (S02) Cross-linking molding: The antioxidant, cross-linking agent, composite shielding agent, stabilizer and rubber compound are mixed, the temperature is increased for cross-linking, and the rubber compound is repeatedly returned to the rubber compound for cooling to obtain a low-carbon, high-temperature resistant and flame-retardant material.
Citation Information
Patent Citations
Waterproof cable
CN104347174A
Thermal shrinkage stress pipe material for third-generation nuclear power station and preparation method of thermal shrinkage stress pipe material
CN104212047A